Screening for Chlamydia trachomatis in secondary schools, family planning and occupational health centres in Luxembourg. Issue 6 (1st July 2009) - Mossong, J; Muller, M; Majéry, N; Mardaga, C; Decruyenaere, F; Schneider, F
Abstract : Background: We conducted a prospective pilot screening study in three settings in Luxembourg where routine urine testing is carried out independently for other purposes with a short sexual behaviour questionnaire to estimate prevalence and determine risk factors of urogenital Chlamydia trachomatis infection. Methods: Screening was offered to sexually active volunteer participants aged less than 25 years in three settings: i) women in three family planning centres (FPC), ii) young women and men in 29 secondary schools and iii) women and men in an occupational health centre (OHC) for newly recruited employees and workers. First catch urine samples were tested using the COBAS Amplicor and an in-house assay. Multiple logistic regression was performed to analyse risk factors. Results: Overall prevalence among 4141 participants was 7.7% (95% CI 6.3 to 9.2) in FPCs, 1.9% (95% CI 1.2 to 2.8) in secondary schools and 4.5% (95% CI 3.5 to 5.6) in the OHC. Depending on the setting, identified risk factors included being 18–22 years old, female sex, having three or more sexual partners in the past year and inconsistent condom use Conclusion: Screening is feasible in the three settings, but the prevalence of C trachomatis infection among men and women is highest in age groups that have left secondary school. Family planning centres were the setting with the highest C trachomatis prevalence and the only setting in our study able to provide case management, follow-up and repeat testing.